Effect of Direct energy surface modification on fatigue life of rotary friction welded Ti6Al4V ELI fatigue coupons. (October 2022) - Tsikayi, D.; Hattingh, D.G.; Bernard, D.; Steuwer, A.; Westraadt, J.; Goosen, W.; Buslaps, T.
Highlights: Shifting initiation sites and increasing fatigue life of small complex shape friction welded components. Near surface material manipulation by laser allowing for the introduction of uniform and homogenous microstructure at the surface, aiding in modifying microstructure variations introduced by friction welding. Achieve a microstructure that inhibits crack initiation in the welded region, improving fatigue life. Abstract: Fatigue crack initiation in engineering components is predominantly associated with tensile surface residual stresses or stress raisers caused by discontinuities or mechanical notches. During welding, surface residual stresses arising from plastic mismatch due to the temperature gradient can accelerate the initiation of cracks during cyclic fatigue testing. Direct energy surface treatment is currently considered a viable post-processing methodology for modifying surfaces within the weld zone to improve fatigue life. This paper discusses results obtained during experimental research, investigating the effect of direct energy surface treatment on surface residual stresses, microstructure, and fatigue life of cylindrical rotary friction welded Ti-6Al-4 V samples. Direct energy post-processing technique aided in improving the fatigue life of friction welded specimens by modifying the surface microstructure, introducing a uniform refined and homogenous structure in the welded region. This near-surface refined microstructure inhibited crack initiation in the welded region, shifting initiation sites to an area adjacent to the modified surface region.